The Cordial Man in Covid-19 Times: Elites, Conflicts in the Public Space and National Characte - Almeida da Silva, Edilson (2023)
Based on a critical rereading of the postulates of two important names of the so-called Brazilian social thought, Sérgio Buarque de Holanda and Roberto DaMatta, our purpose in is to discuss some recent episodes of national repercussion involving conflicts in the Brazilian public space, as well as interactions guided by the adoption of authoritarian practices (for example: “pull rank”). One of the conclusions offered, contrary to what DaMatta suggests, is that “Do you know who you are talking to?” corresponds to one of the faces of cordiality, not to its negation.